INDUSTRI PERDAGANGAN DI INDONESIA: PERKEMBANGAN DAN KINERJA - Cahyadin, Malik; Sutomo, Sutomo; Ratwianingsih, Lely (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
This study aims to describe the development of trade industry in Indonesia. The data covers secondary data that has been published by BPS and BI. Data method uses descriptive qualitative and ratio of market dominance. The analysis showed that: a) the development of trade industry in Indonesia both wholesale and retail tend to be positive / rising especially retail trade; and b) market dominance in the trading industry in Indonesia can be seen from several aspects, are: gender employers (predominantly male entrepreneurs), the company's network (single), the number of employees (permanent), merchandise sales (household) , expenses (purchase of non-food), and income (sales of non-food). Keywords: retail, wholesale, market dominance